Root Capital uses CCAFS data to evaluate 251 loans including 199 for coffee worth 146 million USD - CGIAR Research Program on Climate Change, Agriculture and Food Security (2018)
Root Capital introduced CCAFS data on climate change risk into its process for underwriting and prioritizing loans to producer organizations in cocoa, coffee, and other commodity and food crop supply chains across 20+ countries. CCAFS analysis was translated into a climate change hotspot indicator to inform the underwriting of loans and formally launched in January 2017. To date, the approach has been used to review and close 251 loans, including 199 loans totaling $146 million to coffee and cocoa businesses.